Pengukuran indeks kualitas kebijakan pada pelayanan panggilan kedaruratan 112 di Kota Probolinggo - Fitria, Nurul Jannah Lailatul (PT WIM Solusi Prima, 2024)
Quality policies need to be formed, especially those related to public services that must be carried out by the government through public service innovation through the use of technology. One of the policies that need to be considered is the policy on the use of a single number for emergency calls, 112. Emergency calls for special services to the public who handle emergency conditions. It is this urgency that requires measuring policy quality to find out that policies related to emergency calls are indeed good and deserve to be implemented. As in Probolinggo City, the NTPD 112 service is contained in Mayor Regulation No. 175 of 2019 concerning Amendments to Mayor's Regulation No. 155 of 2018 concerning the Implementation of Services for Probolinggo City Emergency Call Number 112. There are 11 service handling policies in the regulation. Research with descriptive quantitative approach. Researchers conducted research on measuring the quality of the NTPD 112 policy in Probolinggo City with the IKK principle. The research sample was determined by 4 policies from 11 policies through formulas and methods by the State Administration Institute. The measurement uses two variables, namely Policy Planning and Policy Utilization Evaluation with an interval scale measurement of 1-10. The calculation results show that 45% of the value of the Policy Planning process is 3,651 and 55% the value of the Policy Benefit Evaluation process is 4,747. This results in a Policy Quality Index of 8.398. This shows the categorization of the policy quality index. So the quality of the policy for the single number emergency call 112 Probolinggo City is in the